PENGARUH PEMBERIAN FILTRAT DAUN KATUK TERHADAP KONSENTRASI DAN MORFOLOGI NORMAL SPERMATOZOA MENCIT (MUS MUSCULUS) YANG TERPAPAR ASAP ROKOK - RATNA MUSTIKASARI, DWI Ratna; Tjandrakirana, Tjandrakirana (Universitas Negeri Surabaya, 2013)
This research was carried out to prove that the katuk leaves filtrate can improves sperm quality and the concentration of malondialdehyde (MDA) as an indicator of free radicals is lower. The subjects of this reaserch were 60 male mice that were divided into 5 groups; Ko (normal control), K1 (exposured cigarette smoke control), P1 (exposed to cigarrete smoke and given katuk leaves filtrate 2 ml/100 gBW/day), P2 (exposed to cigarette smoke and given katuk leaves filtrate 2.5 ml/100 gBW/day), and P3 (exposed to cigrette smoke and given katuk leaves filtrate 3 ml / 100 gBW/hari). The results showed that katuk leaves filtrate can increase (P <0.05) the concentrations (> 80 million / ml) and normal morphology but the wasn?t difference (P <0.05).